Polyethylene and compositions comprising the same

CN123022718APending Publication Date: 2026-10-30LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580022874.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-09-29
Filing Date
2025-09-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,为了最大限度地减少机械性质的劣化,需要大量的原生树脂,而如环境应力开裂(ESCR)的主要性质的劣化问题仍然没有得到解决

Benefits of technology

根据本发明,通过优化分子结构和密度以优化高分子量区域的比例、低结晶度组分的含量以及可溶性级分的含量,可以提供与再生聚乙烯共混时保持优异机械性质(如落物冲击强度)并改进抗环境应力开裂性的聚乙烯。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a polyethylene which maintains excellent mechanical properties and improves environmental stress cracking resistance when mixed with recycled polyethylene, and a polyethylene composition comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-reference to related applications

[0001] This application claims priority and interest in Korean Patent Application No. 10-2024-0133312, filed on September 30, 2024, and Korean Patent Application No. 10-2025-0141599, filed on September 29, 2025, the entire contents of which are incorporated herein by reference as part of this specification. Technical Field

[0002] This invention relates to a polyethylene that retains excellent mechanical properties and improves resistance to environmental stress cracking when blended with recycled polyethylene. The invention also relates to a polyethylene composition comprising the polyethylene. Background Technology

[0003] The demand for polyethylene resin is steadily increasing, and polyethylene resin is used in a variety of fields.

[0004] In recent years, with increasing public concern for the environment, regulations aimed at reducing carbon dioxide emissions have become increasingly stringent. In particular, environmental pollution caused by the increased use of plastics has created serious problems, leading to stricter regulations at the manufacturing stage, such as mandatory use of recycled resins, especially in the United States. Accordingly, manufacturers must add at least a certain proportion of recycled resin when manufacturing products such as resin-molded articles, and different environmental ratings are assigned to products based on the recycled resin content.

[0005] However, since recycled resin is a pre-processed resin, its properties have been altered by high-temperature processing, and it exhibits significantly lower impact strength, tensile strength, chemical resistance, and thermal stability than virgin resin. To address this issue, attempts have been made to add a predetermined proportion or higher of virgin resin to compositions containing recycled resin. However, to minimize the degradation of mechanical properties, a large amount of virgin resin is required, and the degradation of key properties such as environmental stress cracking (ESCR) remains unresolved. Furthermore, this problem becomes more severe with increasing processing cycles.

[0006] Furthermore, a problem with polyethylene resin products using recycled resin is that it is difficult to simultaneously satisfy mechanical properties and processability, as these are trade-offs.

[0007] Therefore, there is an urgent need to develop a polyethylene as a virgin resin to be blended with this recycled resin, which has excellent mechanical properties and improved resistance to environmental stress cracking. Summary of the Invention

[0008] Technical issues The present invention aims to provide a polyethylene and a polyethylene composition comprising the polyethylene, wherein the polyethylene, when blended with recycled polyethylene, retains excellent mechanical properties, such as drop impact strength, and improves resistance to environmental stress cracking.

[0009] Technical solution According to one embodiment of the present invention, a polyethylene is provided, the polyethylene satisfying the following conditions (1) to (4): (1) The density measured at 23°C according to ASTM D1505 is 0.944 g / cm³. 3 above; (2) In the GPC curve where the x-axis is log Mw and the y-axis is dw / dlogMw, the integral value of the region with a log Mw value of 5.5 or higher is less than 15% of the total integral value; (3) In cross-fractional chromatography (CFC) analysis, the content of the low crystallinity fraction eluted at a temperature of 60 to 90 °C is more than 60% of the total weight of all eluted fractions; (4) In cross-fractional chromatography (CFC) analysis, the content of soluble fractions eluted at a temperature of 20 to 30°C is more than 2.0% of the total weight of all eluted fractions.

[0010] The present invention also provides a polyethylene composition comprising virgin polyethylene (virgin polyethylene or performance-enhanced (Booster) polyethylene) and recycled polyethylene (PCW PE, post-consumer waste polyethylene), wherein the virgin polyethylene comprises the aforementioned polyethylene.

[0011] Beneficial effects According to the present invention, by optimizing the molecular structure and density to optimize the proportion of high molecular weight regions, the content of low crystallinity components and the content of soluble fractions, polyethylene that maintains excellent mechanical properties (such as drop impact strength) and improves resistance to environmental stress cracking when blended with recycled polyethylene can be provided.

[0012] Therefore, when polyethylene is mixed with recycled resin, a recycled polyethylene composition with excellent mechanical properties and improved resistance to environmental stress cracking can be obtained. Detailed Implementation

[0013] In this invention, the terms used in the first and second parts are used to describe various components, and these terms are used only to distinguish one component from another.

[0014] The terminology used herein is for describing exemplary embodiments only and is not intended to limit the invention. Unless the context clearly specifies otherwise, the singular form includes the plural reference. As used herein, terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the stated features, quantities, steps, components, or combinations thereof, and do not exclude the presence or addition of one or more other features, quantities, steps, components, or combinations thereof.

[0015] Furthermore, degree terms such as “approximately” and “substantially” used in this specification are used to refer to: reaching or approaching the specified values ​​in expressing manufacturing and inherent material tolerances in the specified sense, and are used to prevent unlawful infringers from unfairly exploiting the disclosure of precise or absolute values ​​stated to aid in understanding this application.

[0016] The term "parts by weight" as used in this article is a relative concept, indicating the proportion of the weight of one material to the weight of another material. For example, in a mixture containing 50 g of material A, 20 g of material B, and 30 g of material C, based on 100 parts by weight, the amounts of material A, material B, and material C are 40 parts by weight and 60 parts by weight, respectively.

[0017] Furthermore, "wt% (weight percentage)" is an absolute concept, representing the percentage of one material's weight out of the total weight. Taking the mixture above as an example, the contents of materials A, B, and C are 50 wt%, 20 wt%, and 30 wt% of 100% of the total weight of the mixture, respectively. The sum of the contents of all components does not exceed 100 wt%.

[0018] This invention can be modified and taken in various forms, and specific embodiments will be explained and described in detail below. However, it should be understood that this invention is not limited to the specific forms disclosed, but covers all modifications, equivalents, and substitutions that fall within the spirit and scope of this invention.

[0019] The invention will now be described in more detail.

[0020] According to one embodiment of the present invention, a polyethylene is provided in which the molecular structure is optimized along with the density to increase the proportion of high molecular weight regions, the content of low crystallinity components and the content of soluble fractions, thereby maintaining excellent mechanical properties and improving environmental stress cracking resistance (ESCR) even when blended with recycled polyethylene.

[0021] Specifically, the polyethylene of the present invention has a strength of 0.944 g / cm³ as measured at 23°C according to ASTM D1505. 3The density is as follows; in the GPC curve where the x-axis is log Mw and the y-axis is dw / dlogMw, the integral value of the region with a log Mw value of 5.5 or higher is less than 15% of the total integral value; in cross-fractional chromatography (CFC) analysis, the content ratio of the low crystallinity fraction eluted at a temperature of 60 to 90°C is more than 60% of the total weight of all eluted fractions; and in cross-fractional chromatography (CFC) analysis, the content ratio of the soluble fraction eluted at a temperature of 20 to 30°C is more than 2.0% of the total weight of all eluted fractions.

[0022] The polyethylene of the present invention will now be described in more detail.

[0023] Specifically, according to one embodiment of the present invention, the polyethylene may be an ethylene homopolymer or an ethylene / α-olefin copolymer.

[0024] The α-olefin may be at least one selected from the following compounds: 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof.

[0025] For example, the polyethylene according to the present invention may be free of the aforementioned α-olefin, or may contain α-olefin in an amount of 10 wt% or less. That is, the α-olefin may be contained in an amount of 0 to 10 wt% or less. Specifically, the α-olefin may be contained in amounts of 8 wt% or less, 6.5 wt% or less, 5 wt% or less, 4.5 wt% or less, 4 wt% or less, 3.5 wt% or less, 3 wt% or less, 2.5 wt% or less, 2.2 wt% or less, 2 wt% or less, 1.8 wt% or less, or 1.5 wt% or less, but is not limited thereto. When the polyethylene is an ethylene / α-olefin copolymer, the α-olefin may be contained in amounts of 0.1 wt% or more, 0.3 wt% or more, 0.5 wt% or more, 0.7 wt% or more, 0.85 wt% or more, 0.9 wt% or more, 1.0 wt% or more, or 1.2 wt% or more, but is not limited thereto.

[0026] For example, when the polyethylene according to the invention is a copolymer, 1-hexene or 1-butene can be used as an α-olefin copolymerized with ethylene, and more specifically, 1-hexene can be used.

[0027] The polyethylene may be a dry blend of at least one or at least two ethylene homopolymers as described above, or a dry blend of at least one or at least two ethylene / α-olefin copolymers.

[0028] The polyethylene according to one embodiment of the present invention has a strength of 0.944 g / cm³ as measured at 23°C according to ASTM D1505. 3 The above densities.

[0029] More specifically, the density of the polyethylene is 0.944 g / cm³. 3 Above, 0.945 g / cm 3 Above or 0.946 g / cm 3 The above, and 0.965 g / cm 3 Below, 0.964 g / cm 3 Below, 0.963 g / cm 3 Below, 0.962 g / cm 3 Below, 0.961 g / cm 3 Below, 0.960 g / cm 3 Below, 0.959 g / cm 3 Below, 0.958 g / cm 3 Below, 0.957 g / cm 3 Below, 0.956 g / cm 3 Below or 0.955 g / cm 3 the following.

[0030] In this invention, density can be measured according to ASTM D1505, and for example, it can be a value measured at 23°C. For example, the method for measuring density is as described in the following test examples.

[0031] When the density of polyethylene meets the above range, blending it with recycled polyethylene can minimize the deterioration of mechanical properties such as falling impact strength, while improving environmental stress cracking resistance (ESCR).

[0032] Furthermore, in the GPC curve where the x-axis is log Mw and the y-axis is dw / dlogMw, the integral value of the region with a logMw value of 5.5 or higher is less than 15% of the total integral value.

[0033] More specifically, the integral value of a region with a log Mw value of 5.5 or higher can be below 15%, below 14.9%, below 14.8%, below 14.7%, or below 14.6%, and can be above 10%, above 11%, above 12%, or above 13%.

[0034] As described above, by having an integral value ratio of regions with a log Mw value of 5.5 or higher as described above, excellent mechanical properties, such as drop impact strength and processability, can be maintained when blended with recycled polyethylene, and environmental stress cracking resistance (ESCR) can be improved.

[0035] The proportion of regions with a log Mw value greater than 5.5 was measured using gel permeation chromatography (GPC). Specifically, the measurement was performed using gel permeation chromatography (GPC; manufactured by Waters) with a polystyrene equivalent calibration method, and more specific measurement methods are described in the following test examples.

[0036] Furthermore, in cross-fractional chromatography (CFC) analysis of polyethylene, the content of the low crystallinity fraction eluted at temperatures of 60 to 90°C was more than 60% of the total weight of all eluted fractions.

[0037] More specifically, in cross-fractional chromatography, the content ratio of the low crystallinity fraction eluted at a temperature of 60 to 90°C can be above 60%, above 61%, above 62%, above 63%, or above 64%, and can be below 80%, below 79%, below 78%, below 77%, below 76%, below 75%, below 74%, below 73%, below 72%, below 71%, below 70%, below 69%, or below 68%.

[0038] By having a content ratio of low crystallinity fractions as described above, excellent mechanical properties, such as drop impact strength and processability, can be maintained when blended with recycled polyethylene, and environmental stress cracking resistance (ESCR) can be improved.

[0039] Furthermore, in cross-fractional chromatography (CFC) analysis of polyethylene, the content of soluble fractions eluted at a temperature of 20 to 30°C is more than 2.0% of the total weight of all eluted fractions.

[0040] More specifically, in cross-fractional chromatography, the content ratio of soluble fractions eluted at a temperature of 20 to 30°C can be 2% or more, 2.1% or more, 2.2% or more, or 2.3% or more, and can be less than 3.0%, 2.9% or less, 2.8% or less, 2.7% or less, 2.6% or less, or 2.5% or less.

[0041] By having the above-mentioned proportions of soluble fractions, excellent mechanical properties, such as drop impact strength and processability, can be maintained when blended with recycled polyethylene, and environmental stress cracking resistance (ESCR) can be improved.

[0042] In this invention, the content or proportion of low-crystallinity fractions or soluble fractions is calculated based on the total weight of all eluted fractions obtained by cross-fractional chromatography (CFC) analysis, as a percentage (wt%) of the fractions eluted within the corresponding elution temperature range. Specific measurement methods and conditions are described in the following test examples.

[0043] Meanwhile, the polyethylene according to the present invention, while optimizing the molecular structure and density as described above, can have an optimized molecular weight distribution, weight-average molecular weight and melt index, thereby increasing the proportion of high molecular weight regions, the proportion of low crystallinity components and the proportion of soluble fractions.

[0044] Specifically, the polyethylene may have a molecular weight distribution (PDI, Mw / Mn) of 20 to 50. Preferably, the molecular weight distribution (Mw / Mn) of the polyethylene may be 20 or more, 21 or more, or 22 or more, and may be less than 50, less than 49, less than 48, less than 47, less than 46, less than 45, less than 44, less than 43, less than 42, less than 41, less than 40, less than 39, less than 38, less than 37, less than 36, less than 35, less than 34, less than 33, less than 32, less than 31, or less than 30.

[0045] By having the above molecular weight distribution, the proportion of low molecular weight regions in the polyethylene molecular structure can be increased while maintaining the proportion of high molecular weight regions, thereby maintaining excellent mechanical properties when blended with recycled polyethylene and improving environmental stress cracking resistance (ESCR).

[0046] Molecular weight distribution was measured using gel permeation chromatography (GPC). Specifically, it was measured using gel permeation chromatography (GPC; manufactured by Waters Corporation) with polystyrene equivalent calibration.

[0047] Here, the molecular weight distribution can be calculated by measuring the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of polyethylene and dividing the weight-average molecular weight by the number-average molecular weight.

[0048] Specifically, a Waters PL-GPC220 instrument was used as the gel permeation chromatography (GPC) apparatus, employing a Polymer Laboratories PLgel MIX-B column with a length of 300 mm. The measurement temperature was 160 °C, 1,2,4-trichlorobenzene was used as the solvent, and the flow rate was 1 mL / min. Each polyethylene sample was pretreated by dissolving it in a trichlorobenzene solution containing 0.0125% butylated hydroxytoluene (BHT) at 160 °C for 10 hours using the GPC analyzer (PL-GPC220) to a concentration of 10 mg / 10 mL, which was then injected in 200 μL volumes. Mw and Mn values ​​were obtained using a calibration curve derived from polystyrene standards. Nine polystyrene standards with weight-average molecular weights of 2,000 g / mol, 10,000 g / mol, 30,000 g / mol, 70,000 g / mol, 200,000 g / mol, 700,000 g / mol, 2,000,000 g / mol, 4,000,000 g / mol, and 10,000,000 g / mol can be used.

[0049] Polyethylene may have a weight-average molecular weight of 100,000 g / mol to 500,000 g / mol. Preferably, the weight-average molecular weight of the polyethylene may be 100,000 g / mol or more, 105,000 g / mol or more, 110,000 g / mol or more, 115,000 g / mol or more, 120,000 g / mol or more, 121,000 g / mol or more, 122,000 g / mol or more, 123,000 g / mol or more, 124,000 g / mol or more, or 125,000 g / mol or more. However, considering compatibility with recycled polyethylene, the weight-average molecular weight can be below 500,000 g / mol, below 490,000 g / mol, below 480,000 g / mol, below 470,000 g / mol, below 460,000 g / mol, below 450,000 g / mol, below 440,000 g / mol, below 430,000 g / mol, below 420,000 g / mol, below 410,000 g / mol, below 400,000 g / mol, below 390,000 g / mol, below 380,000 g / mol, below 370,000 g / mol, below 360,000 g / mol, below 350,000 g / mol, below 340,000 g / mol, below 330,000 g / mol, below 320,000 g / mol. Below 310,000 g / mol, below 300,000 g / mol, below 290,000 g / mol, below 280,000 g / mol, below 270,000 g / mol, below 260,000 g / mol, below 250,000 g / mol, below 240,000 g / mol, below 230,000 g / mol, below 220,000 g / mol, below 210,000 g / mol, below 200,000 g / mol, below 190,000 g / mol, below 180,000 g / mol, below 170,000 g / mol, below 160,000 g / mol, below 150,000 g / mol, or below 140,000 g / mol.

[0050] By having the above-mentioned weight-average molecular weight, the molecular weight distribution of polyethylene can be optimized, thereby improving environmental stress cracking resistance (ESCR) and obtaining excellent mechanical properties when blended with recycled polyethylene.

[0051] In addition, polyethylene can have a melt index (MI) ranging from 0.1 g / 10 min to 1.5 g / 10 min.2.16 (ASTM D1238, 190°C, 2.16 kg). Preferably, the melt index (MI) of polyethylene is... 2.16 The content can be 0.1 g / 10 min or more, 0.2 g / 10 min or more, 0.3 g / 10 min or more, 0.4 g / 10 min or more, or 0.5 g / 10 min or more, and can be less than 1.5 g / 10 min, less than 1.4 g / 10 min, less than 1.3 g / 10 min, less than 1.2 g / 10 min, less than 1.1 g / 10 min, or less than 1.0 g / 10 min. This is achieved by having a melt index (MI) as described above. 2.16 The polyethylene described herein has excellent compatibility with recycled polyethylene, its molecular weight distribution can be optimized, and when blended with recycled polyethylene, it can improve environmental stress cracking resistance (ESCR) and has excellent mechanical properties.

[0052] Meanwhile, the polyethylene of the present invention can be produced by homopolymerization of ethylene or copolymerization of ethylene with comonomers (e.g., α-olefins) in a slurry circulation process in the presence of a metallocene catalyst, and more detailed synthesis methods can be found in the examples.

[0053] For example, the polyethylene can be prepared by introducing hydrogen in the presence of a catalyst composition comprising a first metallocene compound represented by Formula 1 and two or more second metallocene compounds represented by Formula 2.

[0054] [Chemical Formula 1] (Cp 1 R a ) n (Cp 2 R b M 1 Z 1 3-n In chemical formula 1, M 1 It is a group 4 transition metal; Cp 1 and Cp 2 Each is a cyclopentadienyl group and is C 1-20 Hydrocarbons may be substituted or unsubstituted; R a and R b They may be the same as or different from each other, and each is independently hydrogen or C. 1-20 Alkyl, C 1-20 Alkoxy, C 2-20 Alkoxyalkyl, C 6-20 Aryl, C 6-20 aryloxy group, C2-20 alkenyl, C 7-40 alkylaryl, C 7-40 arylalkyl, C8-40 Aryl alkenyl, C 2-20 Alkyne group or C containing one or more heteroatoms selected from N, O and S 2-20 heteroaryl, provided that R a and R b At least one of them is C 1-20 Alkyl or C 7-20 Arylalkyl, and the other is C 2-20 Alkoxyalkyl; Z 1 Halogen, C 1-20 Alkyl, C 2-20 alkenyl, C 7-40 alkylaryl, C 7-40 Arylalkyl, C 6-20 aryl, substituted or unsubstituted C 1-20 Alkylene, substituted or unsubstituted amino groups, C 2-20 Alkyl alkoxy or C 7-40 arylalkoxy groups; and n is 1 or 0.

[0055] [Chemical Formula 2]

[0056] In chemical formula 2, C1 is any one of the ligands represented by the following chemical formulas 3 to 6; [Chemical Formula 3]

[0057] [Chemical Formula 4]

[0058] [Chemical Formula 5]

[0059] [Chemical Formula 6]

[0060] In chemical formulas 3 to 6, R1 through R6 may be the same as or different from each other, and each is independently hydrogen or carbon. 1-30 Alkyl, C 1-30 Alkoxy, C 2-30 Alkoxyalkyl, C 6-30 Aryl, C 6-30 aryloxy group, C 2-30 alkenyl, C 2-30 alkynyl group, C 3-30 cycloalkyl, C7-40 alkylaryl, C 8-40 alkenylaryl, C 8-40 alkynyl aryl, C 7-40 Arylalkyl, C 8-40 Aryl alkenyl or C 8-40 aryl-alkynyl; M is Ti, Zr, or Hf; Z is -O-, -S-, -NR7-, or -PR7-; R7 is hydrogen, C 1-30 Alkyl, C 6-30 Aryl, C 2-30 alkenyl, C 2-30 alkynyl group, C 3-30 cycloalkyl, C 7-40 alkylaryl, C 8-40 alkenylaryl, C 8-40 alkynyl aryl, C 7-40 Arylalkyl, C 8-40 Aryl alkenyl, C 8-40 Aryl alkynyl, C 1-30 Alkoxysilyl, C 6-30 Aryloxysilyl, C 1-30 Alkyl silyl or C 1-30 Silyl alkyl; X1 and X2 may be the same as or different from each other, and each is independently a halogen or a carbon. 1-30 Alkyl, C 2-30 alkenyl, C 7-30 alkylaryl, C 7-30 Arylalkyl, C 6-20 aryl, substituted or unsubstituted C 1-30 Alkylene, substituted or unsubstituted amino groups, C 2-30 Alkyl alkoxy or C 7-30 arylalkoxy; T is or ; T1 is C, Si, Ge, Sn, or Pb; Y1 is hydrogen, C 1-30 Alkyl, C 1-30 Alkoxy, C 2-30 Alkoxyalkyl, C 6-30 Aryl, C 6-30 aryloxy group, C 2-30 alkenyl, C 2-30 alkynyl group, C 3-30 cycloalkyl, C 7-40 alkylaryl, C 8-40 alkenylaryl, C 8-40 alkynyl aryl, C 7-40 Arylalkyl, C 8-40Aryl alkenyl, C 8-40 Arylynyl, silyl (-SiH3), C 1-30 Alkoxysilyl, C 2-30 Alkoxyalkylsilyl, C 6-30 Aryloxysilyl, C 1-30 Haloalkyl, C 6-30 Halogenated aryl or -NR9R 10 ; Y2 is C 2-30 Alkoxyalkyl or C 7-40 Aryloxyalkyl; R9 and R 10 Each is independently hydrogen, C 1-30 Alkyl, C 6-30 Aryl, C 2-30 alkenyl, C 2-30 alkynyl group, C 3-30 cycloalkyl, C 7-40 alkylaryl, C 8-40 alkenylaryl, C 8-40 alkynyl aryl, C 7-40 Arylalkyl, C 8-40 Aryl alkenyl or C 8-40 Aryl alkynyl groups, or groups linked together to form aliphatic or aromatic rings.

[0061] Unless otherwise specified herein, the following terms may be defined as follows.

[0062] Halogens can be fluorine (F), chlorine (Cl), bromine (Br), or iodine (I).

[0063] C 1-30 Alkyl groups can be straight-chain, branched, or cyclic. Specifically, C 1-20 Alkyl groups can be C 1-15 Straight-chain alkyl; C 1-10 Straight-chain alkyl; C 1-5 Straight-chain alkyl; C 3-20 Branched or cyclic alkyl groups; C 3-15 Branched or cyclic alkyl groups; or C 3-10 Branched or cyclic alkyl groups. More specifically, C 1-20 Alkyl groups can be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, cyclohexyl, etc.

[0064] C 2-30 The alkenyl group can be straight-chain, branched, or cyclic. Specifically, C 2-30 The alkenyl group can be C 2-20 Straight-chain alkenyl, C 2-10 Straight-chain alkenyl, C 2-5 Straight-chain alkenyl, C 3-20Branched alkenyl, C 3-15 Branched alkenyl, C 3-10 Branched alkenyl, C 5-20 Cyclic alkenyl or C 5-10 Cyclic alkenyl groups. More specifically, C 2-20 The alkenyl group can be vinyl, propenyl, butenyl, pentenyl, cyclohexenyl, etc.

[0065] C 6-30 Aryl groups can refer to monocyclic, bicyclic, or tricyclic aromatic hydrocarbons. Specifically, C 6-30 Aryl groups can be phenyl, naphthyl, anthracene, etc.

[0066] C 7-40 Alkyl aryl refers to a substituent in which at least one hydrogen atom of an aryl group is replaced by an alkyl group. Specifically, C 7-40 Alkyl aryl groups can be methylphenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, n-butylphenyl, isobutylphenyl, tert-butylphenyl, cyclohexylphenyl, etc.

[0067] C 7-40 Arylalkyl can refer to a substituent in which at least one hydrogen atom of an alkyl group is replaced by an aryl group. Specifically, C 7-40 Arylalkyl groups can be benzyl, phenylpropyl, phenylhexyl, etc.

[0068] C 1-20 Examples of alkoxy groups include, but are not limited to, methoxy, ethoxy, phenoxy, and cyclohexyloxy.

[0069] C 2-20 An alkoxyalkyl group is a functional group in which at least one hydrogen atom of the aforementioned alkyl group is substituted with an alkoxy group. Specific examples include, but are not limited to, alkoxyalkyl groups such as methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, and tert-butoxyhexyl; and aryloxyalkyl groups such as phenoxyhexyl.

[0070] C 1-20 Alkyl silyl or C 1-20 Alkoxysilyl is a functional group in which one to three hydrogens of -SiH3 are replaced by one to three of the aforementioned alkyl or alkoxy groups. Specific examples include alkylsilyl groups, such as methylsilyl, dimethylsilyl, trimethylsilyl, dimethylethylsilyl, diethylmethylsilyl, and dimethylpropylsilyl; alkoxysilyl groups, such as methoxysilyl, dimethoxysilyl, trimethoxysilyl, and dimethoxyethoxysilyl; and alkoxyalkylsilyl groups, such as methoxydimethylsilyl, diethoxymethylsilyl, and dimethoxypropylsilyl, but not limited thereto.

[0071] C1-20 A silyl group is a functional group in which at least one hydrogen atom of the aforementioned alkyl group is replaced by a silyl group. Specific examples include, but are not limited to, -CH2-SiH3, methylsilylmethyl, dimethylethoxysilylpropyl, etc.

[0072] The sulfonate group has a -O-SO2-R′ structure, where R′ can be C 1-20 Alkyl group. C 1-20 Specific examples of sulfonates include, but are not limited to, methanesulfonates and benzenesulfonates.

[0073] A heteroaryl group is a C group containing at least one of N, O, and S as a heteroatom. 2-20 Heteroaryl groups. Specific examples include xanthyl, thioxanthyl, thiophene, furanyl, pyrrolyl, imidazolyl, thiazolyl, oxazolyl, oxadiazolyl, triazolyl, pyridyl, bipyridyl, pyrimidinyl, triazinyl, acridinel, pyridazinyl, quinolinyl, quinazolinyl, quinoxolinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, pyrazinopyrazinyl, isoquinolinyl, indolyl, carbazole, benzoxazolyl, benzoimidazolyl, benzothiazolyl, benzocarbazole, benzothiaphene, dibenzothiaphene, benzofuranyl, phenanthrololinyl, isoxazolyl, thiadiazolyl, phenothiazinyl, dibenzofuranyl, etc., but are not limited to these.

[0074] The substituents described above may optionally be replaced by at least one substituent selected from the following, within the range that provides the same or similar desired effect: hydroxyl; halogen; alkyl or alkenyl, aryl, or alkoxy; alkyl or alkenyl, aryl, or alkoxy containing at least one heteroatom from Groups 14 to 16; silyl; alkylsilyl or alkoxysilyl; phosphine; phosphide; sulfonate; and sulfone.

[0075] Two adjacent substituents connect with each other to form an aliphatic or aromatic ring. This means that the atoms of the two substituents and the atoms attached to them connect to form a ring. -NR9R 10 R9 and R 10 Specific examples of linkages forming aliphatic rings include piperidinyl groups, and -NR9R 10 R9 and R 10 Examples of linkages that form aromatic rings include pyrrole groups.

[0076] Examples of Group 4 transition metals include titanium (Ti), zirconium (Zr), and hafnium (Hf), but are not limited to these.

[0077] For example, the first metallocene compound represented by chemical formula 1 is one containing the ligand Cp. 1 and Cp 2 Non-bridging compounds. Ligand Cp 1 and Cp2 They can be the same as or different from each other, each is cyclopentadienyl, and can be C 1-10 The alkyl group is substituted once or more, or is substituted one to three times.

[0078] Furthermore, depending on the type of functional group substituted, Cp 1 and Cp 2 Ligands can be used to easily control the characteristics of the prepared olefin polymers, such as chemical structure, molecular weight, molecular weight distribution, mechanical properties, and transparency, by adjusting the degree of steric hindrance. Specifically, Cp 1 and Cp 2 The ligands were respectively R a and R b Replace, where R a and R b They can be the same as or different from each other, and each can independently be a hydrogen atom or a carbon atom. 1-20 Alkyl, C 2-20 Alkoxyalkyl, C 7-40 arylalkyl groups or C groups containing one or more heteroatoms selected from N, O, and S 2-12 heteroaryl; more specifically, it can be C 1-10 Alkyl, C 2-10 Alkoxyalkyl, C 7-20 arylalkyl groups or C groups containing one or more heteroatoms selected from N, O, and S 4-12 Mixed aryl groups. However, R a and R b At least one of them is C 1-20 Alkyl or C 7-20 Arylalkyl, the rest R a and R b At least one of them is C 2-20 Alkoxyalkyl.

[0079] In addition, Cp 1 and Cp 2 There is M between ligands 1 Z 1 3-n And M 1 Z 1 3-n This can affect the storage stability of metal complexes. To more effectively mitigate this effect, each Z... 1 It can be halogen or C independently. 1-20 Alkyl groups, more specifically, can be independently F, Cl, Br, or I. M 1 It can be Ti, Zr, or Hf; Zr or Hf; or Zr.

[0080] In the first transition metal compound, the compound of formula 1 can be such that: where Cp 1 and Cp2 Each is an unsubstituted or substituted cyclopentadienyl group, and R a and R b Each independently is hydrogen, C 1-10 Alkyl, C 2-10 Alkoxyalkyl or C 7-20 arylalkyl, under the condition that R a and R b At least one of them is an alkyl group, such as methyl or butyl, or an arylalkyl group, such as phenylpropyl, and the remaining R a and R b At least one of them is an alkoxyalkyl group, such as tert-butoxyhexyl, more specifically -(CH2). n -OR substituents, where R is a straight-chain or branched alkyl group having 1 to 6 carbon atoms, and n is an integer from 2 to 4.

[0081] Examples of first metallocene compounds represented by chemical formula 1 include, but are not limited to, compounds represented by any of the following structural formulas.

[0082]

[0083] The second metallocene compound contains different ligands, including aromatic ring compounds containing thiophene and basic compounds containing group 14 or 15 atoms. The different ligands are bridged by -T- and there is an M(X1)(X2) between the different ligands.

[0084] More specifically, in chemical formula 2, M is Ti, Zr, or Hf, and more specifically, it can be Ti.

[0085] R1 through R4 are each independently hydrogen or C. 1-20 Alkyl groups, more specifically, can be hydrogen or methyl.

[0086] R5 and R6 are each independently C 1-10 Alkyl groups, and more specifically, R5 and R6 can both be methyl groups.

[0087] Z is -NR7-, where R7 can be C 1-10 Alkyl, and more specifically C 3-10 Branched alkyl groups, such as tert-butyl.

[0088] In addition, T is T1 is C or Si; Y1 is C 1-20 Alkyl, C 1-20 Alkoxy, C 2-20 Alkoxyalkyl, C 6-20 Aryl, C 7-30 alkylaryl, C 7-30 Arylalkyl, C 6-20Aryloxy or C 7-30 Aryloxyalkyl; Y2 is C 2-20 Alkoxyalkyl or C 7-30 Aryloxyalkyl. More specifically, Y1 can be any one of methyl, ethyl, n-propyl, and n-butyl, and Y2 is C. 2-20 Alkoxyalkyl or C 7-30 The aryloxyalkyl group, more specifically, can be any one of methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl, and phenoxyhexyl.

[0089] X1 and X2 are each independently halogenated or C. 1-20 Alkyl groups, more specifically, can be chlorinated or methyl.

[0090] Examples of second metallocene compounds include compounds represented by the following chemical formulas 2a to 2d, wherein the compounds represented by chemical formulas 2a to 2d contain at least two compounds with different structures.

[0091] According to one embodiment of the present invention, as the second metallocene compound, a combination of two compounds represented by the following chemical formulas 2a and 2b, a combination of two compounds represented by the following chemical formulas 2a and 2c, a combination of two compounds represented by the following chemical formulas 2a and 2d, a combination of two compounds represented by the following chemical formulas 2b and 2c, a combination of two compounds represented by the following chemical formulas 2b and 2d, or a combination of two compounds represented by the following chemical formulas 2c and 2d can be used.

[0092] By using a first metallocene compound and a mixture of two or more compounds with different structures selected from those represented by formulas 2a to 2d below as a second metallocene compound, polyethylene with optimized proportions of high molecular weight regions, low crystallinity components, and soluble fractions can be prepared.

[0093] [Chemical Formula 2a]

[0094] [Chemical Formula 2b]

[0095] [Chemical formula 2c]

[0096] [Chemical formula 2d]

[0097] In chemical formulas 2a to 2d, R1 to R7, M, X1, X2, T1, Y1, and Y2 are defined as described above.

[0098] More specifically, the second metallocene compound can be a compound in which M is Ti, Zr, or Hf in formulas 2a to 2d, more specifically Ti; and R1 to R4 are each independently hydrogen or C. 1-20 Alkyl, more specifically hydrogen or methyl; R5 and R6 are each independently C 1-10 Alkyl groups, more specifically R5 and R6 are both methyl groups; R7 is C. 1-10 Alkyl, more specifically C 3-10 Branched alkyl groups, such as tert-butyl; T1 is C or Si; Y1 is C 1-20 Alkyl, C 1-20 Alkoxy, C 2-20 Alkoxyalkyl, C 6-20 Aryl, C 7-30 alkylaryl, C 7-30 Arylalkyl, C 6-20 Aryloxy or C 7-30 Aryloxyalkyl; Y2 is C 2-20 Alkoxyalkyl or C 7-30 Aryloxyalkyl; more specifically, Y1 is any one of methyl, ethyl, n-propyl, and n-butyl, and Y2 is C 2-20 Alkoxyalkyl or C 7-30 Aryloxyalkyl, more specifically, is any one of methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl, and phenoxyhexyl; and X1 and X2 are each independently a halogen or C 1-20 Alkyl, more specifically chlorinated or methyl.

[0099] More specifically, examples of second metallocene compounds include, but are not limited to, compounds having the following structures:

[0100]

[0101] Furthermore, the first and second metallocene compounds in the catalyst composition may be contained in a molar ratio of 1:0.3 to 1:3, and more specifically, in a molar ratio of 1:0.3 or more, 1:0.4 or more, or 1:0.5 or more, and 1:3 or less or 1:2 or less.

[0102] Furthermore, the catalyst composition may contain two second metallocene compounds with different structures in a molar ratio of 1:0.1 to 1:1, and more specifically, in a molar ratio of more than 1:0.1, more than 1:0.2, or more than 1:0.4, and less than 1:1 or less than 1:0.8.

[0103] Additionally, the catalyst composition may further include a support, in which case the first and second metallocene compounds are used in a state supported on the support.

[0104] Specific examples of supports include silicon oxide, aluminum oxide, magnesium oxide, silicon oxide-alumina oxide, silicon oxide-magnesium oxide, etc., which typically further contain oxide, carbonate, sulfate and nitrate components, such as Na2O, K2CO3, BaSO4 and Mg(NO3)2.

[0105] To improve high activity and process stability, the catalyst composition may further include a co-catalyst. More specifically, the co-catalyst may be an alkylaluminoxane-based co-catalyst, such as methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, or butylaluminoxane.

[0106] Meanwhile, in the polyethylene composition according to one embodiment of the present invention, the aforementioned virgin polyethylene is prepared by polymerizing ethylene using the aforementioned catalyst composition. This polymerization process can be carried out as a monomodal (or unimodal) polymerization process, wherein the polymerization reaction is carried out in a single reactor using a single catalyst under a single set of polymerization reaction conditions; more specifically, it can be carried out in a single circulating slurry reactor in the presence of the aforementioned hybrid supported catalyst.

[0107] At this point, the polymerization temperature can be from 25°C to 500°C, preferably from 25°C to 200°C, and more preferably from 50°C to 150°C. The polymerization pressure can be 1 kgf / cm². 2 Up to 100 kgf / cm 2 Preferably 1 kgf / cm 2 Up to 50 kgf / cm 2 More preferably 5 kgf / cm 2 Up to 30 kgf / cm 2 .

[0108] For example, polyethylene can be a dry blend of at least one or at least two ethylene homopolymers prepared separately in the presence of the aforementioned metallocene catalyst; or polyethylene can be a dry blend of at least one or at least two ethylene / α-olefin copolymers.

[0109] Meanwhile, according to another embodiment of the present invention, a polyethylene composition is provided, comprising virgin polyethylene (virgin polyethylene or Booster polyethylene) and recycled polyethylene (PCW PE, post-consumer waste polyethylene), wherein the virgin polyethylene is polyethylene or a mixture thereof according to the foregoing embodiments.

[0110] In particular, as described above, since the polyethylene composition according to the invention uses polyethylene in which the molecular structure and density are optimized together to optimize the proportion of high molecular weight regions, the content of low crystallinity components and the content of soluble fractions, the composition can maintain excellent mechanical properties and improve environmental stress cracking resistance (ESCR) when blended with recycled polyethylene, thereby ensuring excellent drop impact strength and environmental stress cracking resistance close to that of virgin resin even when blended with recycled polyethylene.

[0111] For example, in a polyethylene composition, based on 100 parts by weight of the total composition, virgin polyethylene may be included in an amount of 5 to 20 parts by weight, and recycled polyethylene may be included in an amount of 15 to 50 parts by weight.

[0112] More specifically, in order to improve the ESCR of the polyethylene composition, enhance the effect of reducing carbon dioxide emissions, and achieve properties comparable to virgin resin, the content of virgin polyethylene may be 5 parts by weight or more, or 10 parts by weight or more, and may be 20 parts by weight or less, or 18 parts by weight or less; and the content of recycled polyethylene resin (PCW PE) may be 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more, and may be 50 parts by weight or less, 45 parts by weight or less, or 30 parts by weight or less.

[0113] Meanwhile, the recycled polyethylene (PCW PE) may have a strength of 0.940 g / cm³ as measured at 23°C according to ASTM D1505. 3 Up to 0.960 g / cm 3 The density. More specifically, the density of the recycled polyethylene (PCW PE) may be 0.940 g / cm³. 3 Above, 0.943 g / cm 3 Above, 0.945 g / cm 3 Above, 0.948 g / cm 3 Above or 0.950 g / cm 3 The above, and can be 0.960 g / cm³ 3 Below, 0.958 g / cm 3 Below, 0.956 g / cm 3 Below or 0.955 g / cm 3 the following.

[0114] Furthermore, the recycled polyethylene (PCW PE) may have a melt index (MI) of 0.1 g / 10 min to 0.7 g / 10 min. 2.16 (Measured at 190℃ and under a load of 2.16 kg).

[0115] In addition, the recycled polyethylene (PCW PE) may have an environmental stress cracking resistance (ESCR) of 40 to 60 hours as measured according to ASTM D1693 (condition B, F50, 10% Igepal).

[0116] According to one embodiment of the present invention, the polyethylene composition may further comprise polyethylene having properties different from those of the virgin polyethylene and recycled polyethylene described above. The additional polyethylene is not particularly limited, as long as it is high-density polyethylene (HDPE) compatible with the virgin and recycled polyethylene described above, and commonly used high-density polyethylene and commercially available products can be used. Its content is also not particularly limited, but may be 30 to 80 parts by weight based on 100 parts by weight of the total composition.

[0117] At the same time, the polyethylene composition according to the present invention can ensure excellent ESCR close to that of virgin resin while increasing the content of recycled polyethylene.

[0118] For example, the polyethylene composition may have an environmental stress cracking resistance (ESCR) of more than 200 hours as measured according to ASTM D1693 (condition B, F50, 10% Igepal).

[0119] More specifically, the polyethylene composition may have an environmental stress cracking resistance (ESCR) of more than 200 hours, more than 210 hours, more than 220 hours, more than 230 hours or more, or more than 240 hours, and may have an ESCR of less than 500 hours, less than 400 hours, less than 350 hours or less.

[0120] Furthermore, the polyethylene composition may have a content of 0.940 g / cm³ as measured at 23°C according to ASTM D1505. 3 More specifically, 0.940 g / cm³ 3 Up to 0.960 g / cm 3 The density.

[0121] Currently, the methods for measuring the density, ESCR, etc., of polyethylene compositions are the same as those described above for measuring polyethylene. These methods can also be applied to polyethylene compositions other than polyethylene, so they will not be elaborated further.

[0122] The following are preferred embodiments to aid in understanding the present invention. However, the following embodiments are provided only to aid in understanding the present invention and are not intended to limit the scope of the invention.

[0123] <Example> <Preparation of Polyethylene> Example 1-1 High-density virgin polyethylene is prepared using the following single slurry polymerization process.

[0124] First, isobutane and ethylene were introduced into a single slurry circulation reactor at flow rates of 15 kg / h and 33 kg / h, respectively, and hydrogen was introduced at a flow rate of 300 g / h. A catalyst was introduced in which a first metallocene compound (1), a second metallocene compound (2), and a third metallocene compound (3) were mixed and loaded on a silica support (Grace Davison, SP2212) (molar ratio of first metallocene compound (1): second metallocene compound (2): second metallocene compound (3) = 1:0.41:0.2), and a comonomer (1-hexene) was introduced together. The comonomer used was 1-hexene, and its introduction amount was 3.2 wt% based on the amount of ethylene introduced. At this time, the reactor was maintained at 90 to 95 °C and 42 kg / cm². 3 The copolymerization reaction was carried out under pressure, the solvent was then removed, and the product was passed through a dryer to prepare high-density virgin polyethylene (HDPE) in powder form.

[0125] (1) (2) (3) Examples 1-2 High-density virgin polyethylene was prepared in the same manner as in Example 1-1, except that the hydrogen flow rate in Example 1-1 was changed to 330 g / h and the amount of 1-hexene introduced was changed to 2.8 wt%.

[0126] Examples 1-3 High-density virgin polyethylene was prepared in the same manner as in Example 1-1, except that the hydrogen flow rate in Example 1-1 was changed to 330 g / h and the amount of 1-hexene introduced was changed to 4.0 wt%.

[0127] Comparative Example 1-1 High-density virgin polyethylene is prepared using the following single slurry polymerization process.

[0128] First, isobutane and ethylene were introduced into a single slurry circulation reactor at flow rates of 15 kg / h and 33 kg / h, respectively, and hydrogen was introduced at a flow rate of 220 g / h. A catalyst was introduced in which a first metallocene compound (1) and a second metallocene compound (2) were mixed and loaded on a silica support (Grace Davison, SP2212) (molar ratio of the first metallocene compound to the second metallocene compound = 2:1), and a comonomer (1-hexene) was introduced together. The comonomer used was 1-hexene, introduced in an amount of 1.5 wt% based on the amount of ethylene introduced. At this point, the reactor was maintained at 90 to 95 °C and 42 kg / cm³. 3 The copolymerization process is carried out under pressure, after which the solvent is removed and the product is passed through a dryer to prepare high-density virgin polyethylene (HDPE) in powder form.

[0129] (1) (2) Comparative Examples 1-2 High-density virgin polyethylene was prepared in the same manner as in Comparative Example 1-1, except that the hydrogen flow rate in Comparative Example 1-1 was changed to 240 g / h and the amount of 1-hexene introduced was changed to 1.0 wt%.

[0130] Comparative Examples 1-3 High-density virgin polyethylene was prepared in the same manner as in Comparative Example 1-1, except that the hydrogen flow rate in Comparative Example 1-1 was changed to 160 g / h and the amount of 1-hexene introduced was changed to 0.8 wt%.

[0131] Comparative Examples 1-4 High-density virgin polyethylene was prepared in the same manner as in Comparative Example 1-1, except that the hydrogen flow rate in Comparative Example 1-1 was changed to 300 g / h and the amount of 1-hexene introduced was changed to 2.2 wt%.

[0132] <Preparation of Polyethylene Compositions> Example 2-1 A polyethylene composition (PCR compound) was prepared by dry-blending 10 wt% of the polyethylene prepared in Examples 1-1 as virgin polyethylene, 60 wt% of high-density polyethylene and 30 wt% of recycled polyethylene (PCW PE, post-consumer waste polyethylene) and then extruding it through a twin-screw extruder.

[0133] High-density polyethylene and recycled polyethylene are as follows: High-density polyethylene: Commercially available booster-grade high-density polyethylene (HDPE) products for PCR, prepared using Ziegler-Natta catalyst (Z / N catalyst), product name 6200B, manufactured by Rakuten Chemical Co., Ltd.

[0134] Recycled polyethylene: BSN Hakusan Natural Color product manufactured by Hakusan Plastics Co., Ltd., with a melt index (MI) of 0.15 to 0.2 g / 10min. 2.16 (Measured according to ASTM D1238 (Condition E) at 190°C and 2.16 kg load), 0.951 to 0.953 g / cm³ 3 The density (measured according to ASTM D1505), and the ESCR (time to reach F50 (50% failure) after 40 to 50 hours, measured according to ASTM D1693 at 50°C using a 10% Igepal CO-630 solution).

[0135] Example 2-2 The polyethylene compositions were prepared in the same manner as in Examples 2-1, except that the polyethylene prepared in Examples 1-2 was used instead of the polyethylene prepared in Examples 1-1 as the virgin polyethylene.

[0136] Example 2-3 The polyethylene compositions were prepared in the same manner as in Examples 2-1, except that the polyethylene prepared in Examples 1-3 was used instead of the polyethylene prepared in Example 1-1 as the virgin polyethylene.

[0137] Comparative Example 2-1 The polyethylene composition was prepared in the same manner as in Example 2-1, except that the polyethylene prepared in Comparative Example 1-1 was used instead of the polyethylene prepared in Example 1-1 as the virgin polyethylene.

[0138] Comparative Example 2-2 The polyethylene compositions were prepared in the same manner as in Examples 2-1, except that the polyethylene prepared in Comparative Examples 1-2 was used instead of the polyethylene prepared in Examples 1-1 as the virgin polyethylene.

[0139] Comparative Examples 2-3 The polyethylene compositions were prepared in the same manner as in Examples 2-1, except that the polyethylene prepared in Comparative Examples 1-3 was used instead of the polyethylene prepared in Examples 1-1 as the virgin polyethylene.

[0140] Comparative Examples 2-4 The polyethylene compositions were prepared in the same manner as in Examples 2-1, except that the polyethylene prepared in Comparative Examples 1-4 was used instead of the polyethylene prepared in Examples 1-1 as the virgin polyethylene.

[0141] <Test Example: Evaluation of Polyethylene Properties> The properties of the polyethylene or polyethylene compositions of the examples and comparative examples were evaluated using the following methods, and the measurement results are shown in Tables 1 and 2 below.

[0142] (1) Density The density (g / cm³) of polyethylene was measured at 23°C according to ASTM D1505. 3 ).

[0143] (2) Weight-average molecular weight (Mw), molecular weight distribution (PDI, Mw / Mn), and content with log Mw ≥ 5.5 The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of polyethylene were measured using gel permeation chromatography (GPC; manufactured by Waters Corporation), and the molecular weight distribution (PDI, Mw / Mn) was calculated by dividing the weight-average molecular weight by the number-average molecular weight.

[0144] Specifically, a Waters PL-GPC220 instrument was used as the gel permeation chromatography (GPC) instrument, employing a Polymer Laboratories PLgel MIX-B column with a length of 300 mm. The measurement temperature was 160 °C, 1,2,4-trichlorobenzene was used as the solvent, and the flow rate was 1 mL / min. Polyethylene samples according to the examples and comparative examples were pretreated using the GPC analyzer (PL-GPC220) by dissolving them in trichlorobenzene containing 0.0125% butylated hydroxytoluene (BHT) at 160 °C for 10 hours to prepare a concentration of 10 mg / 10 mL, which was then injected in 200 μL volumes. Mw and Mn values ​​were obtained using a calibration curve based on polystyrene standards. Nine polystyrene standards with weight-average molecular weights of 2,000 g / mol, 10,000 g / mol, 30,000 g / mol, 70,000 g / mol, 200,000 g / mol, 700,000 g / mol, 2,000,000 g / mol, 4,000,000 g / mol, and 10,000,000 g / mol were used.

[0145] Using the method described above, gel permeation chromatography (GPC; manufactured by Waters) is used to represent the region with a log Mw value greater than 5.5 (log Mw ≥ 5.5) as a percentage of the total area of ​​the GPC analysis curve (where the y-axis is dw / dlogMw and the x-axis is log Mw).

[0146] (3) Content of low crystallinity fraction and soluble fraction The polyethylene samples from the examples and comparative examples were analyzed by cross-gradient chromatography (CFC) using the following method.

[0147] -Analytical instrument: Polymer Char CFC-7890B (G3440D) (Detector: Integrated IR5 MCT detector) - Sample preparation and introduction: 32 mg of polyethylene from each example or comparative example was placed in a 10 mL sample vial and placed in an autosampler. 8 mL of 1,2,4-trichlorobenzene (TCB) was added. The polyethylene was dissolved at 160 °C for 90 min and then stabilized at 140 °C for 20 min. The resulting solution was extracted after purging with nitrogen and loaded onto a temperature-eluting fractionation column (TREF column).

[0148] - Crystallization: After adjusting the temperature of the sample loaded onto the TREF column to 140°C, cool the sample from 140°C to 35°C at a rate of 0.5°C / min and hold for 15 minutes.

[0149] The detailed stabilization and crystallization conditions are as follows:

[0150] - Temperature-elution fractionation (TREF) analysis: The crystallized sample was heated from 35°C to 120°C at a rate of 20°C / min, and the following fraction temperatures were reached and maintained sequentially. The concentration of the fraction eluted for 5 minutes at the corresponding temperature was measured. The TREF plot was obtained from these concentration measurements.

[0151] From the TREF plot, based on the total weight of all eluted fractions, the content ratio of low crystallinity fractions eluted in the elution temperature range of 60 to 90 °C and the content of soluble fractions eluted in the elution temperature range of 20 to 30 °C were calculated.

[0152] <Graded Temperature> 35℃ / 40℃ / 43℃ / 46℃ / 49℃ / 52℃ / 55℃ / 58℃ / 61℃ / 64℃ / 67℃ / 70℃ / 73℃ / 76℃ / 79℃ / 82℃ / 85℃ / 88℃ / 91℃ / 94℃ / 97℃ / 100℃ / 105℃ / 120℃ (4) Environmental stress cracking resistance (ESCR) According to ASTM D1693-07, under condition B at 50°C, the time it takes for each polyethylene composition (PCR compound) to reach F50 (50% failure) is measured using a 10% Igepal CO-630 solution.

[0153] (5) Falling object impact Discs were prepared based on each polyethylene resin composition (PCR compound) using the following method.

[0154] More specifically, a disc was prepared using an injection molding machine. After setting the injection molding machine to have a temperature gradient of 210 to 230°C, a polyethylene resin composition was injected and injection molded at an injection speed of 11 mm / s and a holding pressure of 450 bar to prepare a disc with a diameter of 50 mm and a thickness of 2 mm.

[0155] For the prepared disc, its drop impact strength, corresponding to its surface impact strength, was measured according to ASTM D3763. Specifically, using an Instron 9440 drop tower, under conditions of 4.2 J impact energy, 4.55 m / s impact velocity, and 5°C, the disc was fixed and a weight was dropped, and the number of drops until cracks appeared was measured.

[0156] (6) Melt Index (MI) 2.16 ) Melt index was measured according to ASTM D1238 at 190°C and a load of 2.16 kg.

[0157] [Table 1]

[0158] [Table 2]

[0159] Referring to Tables 1 and 2, it can be seen that when using virgin polyethylene according to Examples 1-1 to 1-3 of the present invention, its molecular structure and density are optimized together to optimize the proportion of high molecular weight regions, the content of low crystallinity components and the content of soluble fractions. When blended with recycled polyethylene (PCW PE), it maintains excellent mechanical properties, such as drop impact strength, while the environmental stress cracking resistance (ESCR) is significantly improved to more than 200 hours.

Claims

1. Polyethylene that meets the following conditions (1) to (4): (1) The density measured at 23°C according to ASTM D1505 is 0.944 g / cm³. 3 above; (2) In the GPC curve where the x-axis is log Mw and the y-axis is dw / dlogMw, the integral value of the region with a log Mw value of 5.5 or higher is less than 15% of the total integral value; (3) In cross-fractional chromatography (CFC) analysis, the content of the low crystallinity fraction eluted at a temperature of 60 to 90 °C is more than 60% of the total weight of all eluted fractions; (4) In cross-fractional chromatography (CFC) analysis, the content of soluble fractions eluted at a temperature of 20 to 30°C is more than 2.0% of the total weight of all eluted fractions.

2. The polyethylene according to claim 1, The polyethylene therein is an ethylene homopolymer or an ethylene / α-olefin copolymer.

3. The polyethylene according to claim 2, in, The α-olefin is selected from at least one of the following compounds: 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof.

4. The polyethylene according to claim 1, in, In a GPC curve where the x-axis is log Mw and the y-axis is dw / dlogMw, the integral value of the region with a log Mw value of 5.5 or higher is 10% to 15% of the total integral value.

5. The polyethylene according to claim 1, in, In cross-fractional chromatography (CFC) analysis of polyethylene, the content of the low crystallinity fraction eluted at a temperature of 60 to 90°C is 60% to 80% of the total weight of all eluted fractions.

6. The polyethylene according to claim 1, in, In cross-fractional chromatography (CFC) analysis of polyethylene, the content of soluble fractions eluted at a temperature of 20 to 30°C is 2.0% to 3.0% of the total weight of all eluted fractions.

7. A polyethylene composition comprising virgin polyethylene and recycled polyethylene (PCW PE, post-consumer waste polyethylene). in, The virgin polyethylene is the polyethylene according to any one of claims 1 to 6, or a mixture thereof.

8. The polyethylene composition according to claim 7, in, Based on 100 parts by weight of the total composition, the virgin polyethylene is contained in an amount of 5 to 20 parts by weight, and The recycled polyethylene is contained in an amount of 15 to 50 parts by weight, based on 100 parts by weight of the total composition.

9. The polyethylene composition according to claim 7, in, The recycled polyethylene has a strength of 0.940 to 0.960 g / cm³ as measured at 23°C according to ASTM D1505. 3 The density.

10. The polyethylene composition according to claim 7, in, The recycled polyethylene has an environmental stress cracking resistance (ESCR) of 40 to 60 hours as measured according to ASTM D1693 (Condition B, F50, 10% Igepal).

11. The polyethylene composition according to claim 7, in, The recycled polyethylene has a melt index (MI) of 0.1 g / 10 min to 0.7 g / 10 min. 2.16 The measurements were taken at 190°C and under a load of 2.16 kg.

12. The polyethylene composition according to claim 7, in, The polyethylene composition has an environmental stress cracking resistance (ESCR) of more than 200 hours as measured according to ASTM D1693 (condition B, F50, 10% Igepal).

Citation Information

Patent Citations

  • Highly-durable conductive fiber with retained electrical properties after washing and its manufacturing method

    KR1020240133312A

  • Electrochemical treatment method for recycling secondary battery

    KR1020250141599A